Virtual Reality as Treatment Method for Knee Osteoarthritis - Short Review (Journal of Pharmaceutical Negative Results, 2022)
Virtual reality is computer-generated technology for therapeutic uses and rapidly growing in popularity. This review focused on the outcomes of the study show that virtual reality as treatment approach is a safe and acceptable therapy providing participants with satisfaction and motivation to exercise. Therapists are using VR to help people rehabilitate from osteoarthritis, strokes and injuries. The efficiency of Virtual Reality treatment was observed in patient with OA knee and many other diseases. Virtual reality approach Physical rehabilitation focuses on pain treatment, gait re-education, body balance improvement, increased mobility, and muscular strength development. Because of VR and modern technology, this activity should be done quickly and safely under the supervision of the therapist. Virtual reality is cost-effective of VR headsets and the expansion of Virtual reality apps. Using virtual reality to create fascinating and demanding settings can help you active and interested in your rehab.